Praying the Psalms and the Challenges of Christian–Jewish Relations: Dietrich Bonhoeffer and Thomas Merton - Worthen, Jeremy (Studies in Christian-Jewish Relations, 2014)
Dietrich Bonhoeffer and Thomas Merton both published works on the Psalms that expressed their deep commitment to prayerful reading of the Psalter as integral to Christian spirituality. This article sets out some of the central themes in each case and argues that there are important and creative connections for both of these influential figures between how they prayed the Psalms and how they engaged with the challenges in Christian-Jewish relations that they discerned in their overlapping but also contrasting contexts. In particular, the practice of praying the Psalms fostered an openness to identification with other persons that was both hermeneutical and spiritual, shaping the different ways in which they came to sketch out new forms of Christian identification with Jewish experience.